A novel technique for submucosal tumors in the esophagus: mucosal zipper endoscopic resection - Luo, Zhenkai; Yu, Jiangping; Zhang, Hui; Yang, Shaopeng; Li, Jian; Liu, Jianling; Wang, Shi (Endoscopy, 2025)
The mucosal zipper endoscopic resection (MZER) technique was developed as a novel approach for treating esophageal submucosal tumors (SMTs). This study aims to introduce the MZER technique and evaluate its feasibility.This retrospective study included 24 patients who underwent MZER between January 2022 and January 2024. Clinical data and treatment outcomes were collected and analyzed.Among these patients, the median distance from the incisor teeth to the SMTs was 25 cm (range: 16–38 cm), the median tumor length was 3.0 cm (range: 2.2–7.0 cm) and the median tumor width was 2.2 cm (range: 1.8–4.0 cm). All esophageal SMTs were successfully resected, achieving an en bloc resection rate of 100%. Intra-procedural perforation occurred in 10 patients (41.7%). The median operation time was 50 minutes (range: 30–180 minutes), and the median duration of hospitalization was 3 days (range: 2–6 days). No delayed bleeding or perforation occurred.MZER seems to provide an optional treatment for proximal or larger esophageal SMTs. The efficacy and safety profiles need further validation through multicenter studies with larger cohorts, given the current limitations of sample size and single-center design.